Pelaksanaan Pemberian Perlindungan Bagi Korban Tinda Pidana Terorisme - Jeanne Darc Noviayanti Manik; Rahmat Robuwan; Wirazilmustaan Wirazilmustaan (PROGRESIF: Jurnal Hukum, 2022)
Victims of terrorism are not only those affected by terrorist attacks but include those exposed to terrorist ideology. The series of bombings, shootings and stabbings that occurred in the territory of the Republic of Indonesia has resulted in the loss of life regardless of the victim, causing widespread public fear, and property losses, resulting in a wide impact on social, economic, political, and international relations. The method used is Legal Research based on legislation related to each other. The best thing that can be done by the state to maintain the safety and security of citizens from becoming victims of terrorism is to prevent or anticipate that terrorism crimes do not occur. The fulfillment of the rights of victims under Act No. 15 of 2003 at the crisis stage after the crime of terrorism must be taken immediately because the action relates to the safety of the victim. Act No. 5 of 2018 states that the victim of non-criminal terrorism is a person who suffers physical, mental, and/or economic losses resulting from a Terrorism Crime. Victims are direct victims as well as indirect victims of a crime of terrorism. The determination of victims of terrorism can be done directly by investigators, without having to wait for a court decision. Treatment of victims, especially those who must receive medical treatment, psychosocial and psychological rehabilitation.